The Gen Z Movement in the Face of the Anti-Corruption Crisis - Rahimah, Aisyah; Handrian, Muhammad Diandy; Ramadani, Dinda Putri; Saputri, Hernisa; Diba, Farah; Khairunnisa, Dinda; Luthfiardi (Borneo Novelty Publishing, 2025)
Purpose: This study aims to analyze the involvement and impact of Generation Z (Gen Z) in the anti-corruption movement in Indonesia. The main focus is to understand how Gen Z, as a generation that grew up in the digital era with high social awareness, participates in efforts to combat corruption.Research Methodology / Design / Approach: The study uses a qualitative descriptive approach with a comprehensive literature analysis from various sources such as journals, research articles, media coverage, and publications of anti-corruption organizations. Data are systematically analyzed through collection, classification based on key themes, and synthesis to understand the role and contribution of Gen Z in eradicating corruption.Findings: Gen Z shows an active and innovative role in the anti-corruption movement by utilizing digital technology and social media for campaigns, mass organizing, and raising public awareness. They face various obstacles such as opposition from established systems and limited funds, but remain persistent in their struggle. Gen Z also collaborates with various stakeholders to strengthen accountability and transparency, and emphasizes the importance of anti-corruption education.Originality / Value: This study provides new insights into the strategic role of Gen Z as agents of change in eradicating corruption in Indonesia. With their creative and technologically advanced approaches, Gen Z offers fresh perspectives and great potential to build more effective and sustainable anti-corruption campaigns, supported by cross-generational and cross-sector collaboration.